2019
DOI: 10.1177/2320206819886141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surface Roughness of Composite, Compomer and Carbomer After Curing Through Mylar Strip and Glycerin: A Comparative Study

Abstract: Aim: To compare the effect of mylar strip and glycerin topical application on the surface roughness of composite, compomer, and carbomer during polymerization. Materials and Method: Each of 45 disc-shaped specimens of Z250, Dyract, Carbomer, were prepared according to manufacturer’s instructions and molded in silicone rubber molds by one operator (5 mm diameter × 2 mm thickness; n = 135). Each restorative group was divided into 3 groups as oxygen group (control), mylar strip, and glycerin group (n = 15). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Also, it is possible to say that the surface of test specimens was still rich in unreacted monomers when finishing and polishing were not performed, although clinicians usually think that the use of matrix strips prevented the formation of an oxygen inhibition zone. In line with previous studies [ 11 , 12 ], this study showed that Mylar strips may minimize the formation OIL, but finishing and polishing procedures are still essential for the elimination of the resin-rich outer layer that can be the source of the unreacted monomers eluted to the oral cavity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also, it is possible to say that the surface of test specimens was still rich in unreacted monomers when finishing and polishing were not performed, although clinicians usually think that the use of matrix strips prevented the formation of an oxygen inhibition zone. In line with previous studies [ 11 , 12 ], this study showed that Mylar strips may minimize the formation OIL, but finishing and polishing procedures are still essential for the elimination of the resin-rich outer layer that can be the source of the unreacted monomers eluted to the oral cavity.…”
Section: Discussionsupporting
confidence: 88%
“…OIL could be minimized by blocking air contact with the use of matrix strips or glycerin before curing; however, since there is oxygen already present within the resin material, the most effective method to eliminate the OIL is to finish and polish the surface after curing [8,9]. Finishing and polishing procedures are also essential for the elimination of the resin-rich outer surface [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…At this point, results suggest that it is equally effective to photocure through an intermediate layer of glycerin manufactured for specific dental use as it is to photocure without any protection to stop the oxygen-free radicals present in the air that produces OIL formation. A previous study confirms that there were no significant differences in the surface hardness of samples protected with various methods to neutralize free oxygen, and other authors agree with this line of results regarding surface roughness (38,39).…”
Section: Discussionsupporting
confidence: 78%
“…Studies have shown that inadequate polymerization can affect the hardness and roughness of the material and influence biofilm retention, favoring gingival inflammation, secondary caries formation, and superficial staining, thereby compromising the longevity of the restoration (30). In that regard application of glycerin has been recommended as a method to improve surface polymerization by inhibiting the formation of OIL in composite resins for direct restorations (6,10,(31)(32)(33) and threedimensional printing (34). Glycerin (C3H8O3) or glycerol 1,2,3-propanediol is a colorless, odorless, and viscous liquid alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent the formation of an oxygen inhibited layer during the cement polymerization, a celluloid strip was positioned over every specimen of resin cement before the curing procedure 30 . The tip of the light cure was placed directly on the ceramic sample to ensure optimal transmission and penetration of light through the specimens 31 .…”
Section: Discussionmentioning
confidence: 99%